Developing a Integrated Marketing Communication Plan for Educational Services of VTCE Education Development Investment Joint Stock Company - Vu, Tran Nguyet Khanh (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.